Efficacy of dabigatran versus warfarin in patients with acute venous thromboembolism in the presence of thrombophilia: Findings from RE-COVER®, RE-COVER™ II, and RE-MEDY™ - Goldhaber, Samuel Zachary; Feuring, Martin (Vascular medicine, 2016)
It is unclear whether thrombophilia causes resistance to anticoagulant therapy. Post hoc analyses of data from RE-COVER®, RE-COVER™ II, and RE-MEDY™ were performed to compare dabigatran etexilate with warfarin for the treatment and prevention of venous thromboembolism (VTE) in patients with thrombophilia or antiphospholipid antibody syndrome (APS). There were no significant differences in symptomatic VTE/VTE-related deaths between dabigatran etexilate and warfarin in patients with or without thrombophilia. All bleeding event categories were less frequent with dabigatran etexilate than with warfarin, regardless of whether patients had thrombophilia, no thrombophilia, or were not tested. However, these differences did not reach significance in every group. In patients with APS, there was no significant difference in VTE/VTE-related deaths between the two treatment arms. Rates of bleeding events tended to be lower with dabigatran etexilate than with warfarin, reaching statistical significance for any bleeding event. In conclusion, the efficacy and safety of dabigatran etexilate were not significantly affected by the presence of thrombophilia or APS. ClinicalTrials.govRECOVER Identifier: NCT00291330; RECOVER II Identifier: NCT00680186; RE-MEDY Identifier: NCT00329238
Gesehen am 30.10.2019